Synthesis of Cobalt Oxides Thin Films Fractal Structures by Laser Chemical Vapor Deposition - P. Haniam; C. Kunsombat; S. Chiangga; A. Songsasen (The Scientific World Journal)
Thin films of cobalt oxides (CoO and Co3O4) fractal structures have been synthesized by using laser chemical vapor deposition at room temperature and atmospheric pressure. Various factors which affect the density and crystallization of cobalt oxides fractal shapes have been examined. We show that the fractal structures can be described by diffusion-limited aggregation model and discuss a new possibility to control the fractal structures.